The Effectiveness of Learning Management System in the Student Learning Process in the Pandemic Era of the Covid-19 - Nurul Qamarya; Nour Sriyanah; Lumastari Ajeng Wijayanti; Iramaya Sari; Suprapto Suprapto (Postgraduate, University of Mataram, 2023)
The purpose of the study is to determine the effectiveness of the learning management system in improving the ability of the student learning process. This research is a quantitative descriptive study. The data analysis used is to use the one-sample t-test. The data normality test is carried out before the test of one sample t-test as a prerequisite. The sample in this study was 35 students. The results showed that the average student activity while using the learning management system in the learning process of the teaching material development course has increased. In addition, the average ability score of students who obtain learning using the learning management system > 77 is met so that it can be said to be effective. Based on the results of the normality test calculations shows that the normal distribution data with a Shapiro-Wilk significance of 0.060 > 0.05. Meanwhile, based on the One Sample t-test shows that the learning management system significantly impacts students' abilities with a significance value of 0.005 < 0.05, which means that the learning management system is effectively used in the learning process.